Pengembangan Lembar Kerja Siswa Menggunakan PMRI untuk Mengukur Kemampuan Pemecahan Masalah Matematis Siswa - Luthafiana, Maria; Refianti, Rani; Elly, As (Jurnal Pendidikan Matematika : Judika Education, 2024)
The purpose of this study was to develop student worksheets using a valid and practical Indonesian realistic approach and to determine the mathematical problem-solving abilities of junior high school students. This study is a development research using the 4D development model. The subjects in this study were students of SMP Negeri 13 Lubuklinggau class VII in the 2023/2024 academic year. Based on the results of the development research, it can be drawn that the results of the LKS developed were based on the validation of the validation questionnaire by the language validator. While for media validation, it is also in the valid category. For the practicality LKS developed, it is in the practical category based on the assessment of the practicality questionnaire given to students in small groups, namely 80.05% and based on the teacher's practicality assessment, it is in the practical category with a practicality percentage of 80%. Based on the test results given to 28 students of grade VII, data was obtained that for indicator number one, namely understanding the problem, it has a percentage of 66% included in the high category, for indicator number two, namely the indicator Determining the right plan, it has a percentage of 58% included in the sufficient category, for indicator number three, implementing the plan, it has a percentage of 53% included in the sufficient category, for indicator number four, it has a percentage of 51% included in the sufficient category. In conclusion, the LKS developed using the PMRI approach is declared valid both in terms of development and media, practical and able to meet the specified indicators. Keywords: Development, Student worksheets, PMRI Approach